The anterior cingulate cortex mediates processing selection in the Stroop attentional conflict paradigm. - Pardo, J V (1990)
Regional cerebral blood flow, an index of local neuronal activity, was measured using positron emission tomography (PET) during the performance of the classic Stroop color/word task in eight healthy right-handed subjects. In the first condition of this paradigm, subjects name the color of the words presented on a video monitor. All the words are the color names congruent to the color presented (e.g., the noun "red" displayed in red color). In the second condition, subjects also name the color of the words presented on the monitor. However, during these trials all words are color names incongruent to the color presented (e.g., the noun "red" displayed in green color). The difference in brain activity between these two conditions (i.e., incongruent minus congruent) could reveal brain systems involved in the attentionally mediated resolution of the conflict between the habitual response of reading words vs. the task demands of naming the color of the words--i.e., the Stroop interference effect. The most robust responses occurred in the anterior cingulate cortex. Other responses noted were in the left premotor cortex, left postcentral cortex, left putamen, supplementary motor area, right superior temporal gyrus, and bilateral peristriate cortices. These data provide support for the role of the anterior cingulate cortex in attentional processing through the selection and recruitment of processing centers appropriate for task execution. Furthermore, the extensive distributed network of activated regions suggests that the Stroop interference effect cannot be explained simply in terms of stimulus encoding or response interference.